PERAN SOSIALISASI PAJAK DALAM MEMEDIASI PENGARUH PENGETAHUAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO - Safara Nur Oktaviani; Khoirina Farina (Universitas Trilogi, 2026)
This study aims to analyze the effect of tax knowledge, tax sanctions, and tax socialization on the level of MSME taxpayer compliance. The population in this study was unknown with certainty; therefore, the sample size was determined using the Lemeshow formula, resulting in 101 respondents. The sampling technique employed was accidental sampling, in which respondents were selected incidentally based on the predetermined research criteria. Data analysis was conducted using multiple linear regression analysis to examine the relationship and influence of the independent variables on the dependent variable. The results indicate that tax knowledge does not have a significant effect on taxpayer compliance. However, tax knowledge indirectly affects taxpayer compliance through the mediating role of tax socialization. Furthermore, tax sanctions have a significant effect on taxpayer compliance, but do not indirectly affect taxpayer compliance through tax socialization. Meanwhile, tax socialization does not have a significant effect on taxpayer compliance.Keywords: Taxpayer Compliance; Tax Knowledge; Tax Sanctions; Tax Socialization; MSME Taxpayers